Bataille's Peak : Energy, Religion, and Postsustainability - Stoekl, Allan (Book collections on Project MUSE., 2007)
In Bataille's Peak, Allan Stoekl demonstrates how a close reading of Georges Bataille can help us rethink not only energy and consumption but also such related topics as the city, eroticism, and religion. The challenge of living in the twenty-first century, Stoekl argues, will be to comprehend the inevitable shift from a civilization founded on waste to one based on Bataillean expenditure.